DAMPAK PENERAPAN SISTEM ABSENSI FINGER PRINT DAN PUNISHMENT TERHADAP KINERJA KARYAWAN DENGAN DISIPLIN KERJA SEBAGAI VARIABEL MEDIASI DI STIKES SENIOR MEDAN - Nasution, Miftahul Jannah; Bulan, Tapi Rondang Ni; Setiawan , Teguh (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study was conducted at STIKES Senior Medan, an educational institution, to examine the effect of implementing a fingerprint attendance system and punishment, both partially and simultaneously, on employee performance mediated by work discipline. The research subjects included all employees working at STIKES Senior Medan, totaling 125 people. The sampling technique was carried out by census, meaning that the entire population was used as respondents. Primary data was obtained by distributing questionnaires to all respondents. Data analysis includes data quality tests, path analysis, regression assumption tests, and hypothesis testing. The results of the data analysis show that the fingerprint attendance system has a significant influence on the application of sanctions on employee work discipline. In addition, a high level of work discipline plays an important role in improving employee performance. The results showed that work discipline acts as a mediating factor that strengthens the relationship between the application of the fingerprint attendance system and the application of sanctions with employee performance at STIKES Senior Medan. When examined together, the implementation of the fingerprint attendance system and the application of sanctions have a significant effect on employee work discipline. In addition, the combination of the three variables - fingerprint attendance, work discipline, and sanctions - also significantly affected employee performance. This study found a strong relationship between the use of the fingerprint attendance system and the application of sanctions to employee work discipline. An equally strong relationship was also found between the combination of the three variables and employee performance. About 52.9% of the variation in employee work discipline at STIKES Senior Medan can be explained by the influence of the fingerprint attendance system and the application of sanctions. Meanwhile, about 59.7% of the variation in employee performance can be explained by the combination of the three variables. At the same time, the rest is influenced by other factors that are not measured in this study.